A116 ASSESSING THE EFFECTIVENESS OF THE NURSE NAVIGATOR ROLE IN AN IBD MEDICAL HOME: A RETROSPECTIVE COHORT STUDY. (26th February 2020) - Gawdat, K; Heisler, C; Nazer, N; Stewart, M; Currie, B; Phalen-Kelly, K; Jones, J
Abstract: Background: Patients living with chronic illnesses require long-term and often repeated interactions with the healthcare system. Inflammatory Bowel Disease (IBD) is an incurable, chronic gastrointestinal disease which frequently flares and remits. The nurse navigator (NN) serves as the point of first contact for IBD connecting patients with their multidisciplinary care team in order facilitate and expedite assessment, treatment and navigation through the healthcare system with the goal of improving disease-related outcomes while reducing healthcare system burden. Aims: The aim of this study was to assess the impact of implementation of an IBD NN role within a multidisciplinary IBD Medical home on access to care, disease related outcomes, patient satisfaction with care, and healthcare resource use. Methods: This was a retrospective cohort study comparing an IBD patient population that had access to a 24/7 NN-led helpline to a reference population who did not have access to such a service. Data between August 2017 and October 2019 were extracted from patient charts. Distribution of number of flares and time to clinical assessment between the NN exposed cohort and a non-NN exposed cohort are planned using multivariate analysis. This is a preliminary description of the NN-exposed cohort only. Results: Preliminary results identified a total of 643 patients in the NN-exposed cohort. The majority of our NN-exposed population were female (64.3%). The mean age was 46.42 ± 16.86 years. Sixty-five percent of patients had CD, 33% UC and 2% IBDU. Of the 729 calls extracted, care coordination (39%) was the most frequent indication for calls followed by flare (25%), and medication education (16%). Patients made the majority (52.8%) of calls compared to NN initiated calls (47.2%). The mean number of calls per patient was 2.64 ± 2.51 (range 1–18) during the study period. Time to clinic assessment post flare call was on average 10.22 ± 8.51 days. Conclusions: These results are descriptive of the NN-exposed cohort. Data comparing outcomes amongst the NN-exposed cohort to the non-exposed cohort will be presented at CDDW. Funding Agencies: None